Development and research of an electrical control system for the electric drive of a cascade pumping unit - Ramsh, V.; Kolodiichuk, L.; Kondrat, O. (Energy and Automation, 2026)
The paper presents the results of a study of an automated control system for a cascade pumping unit with variable-frequency electric drive control aimed at improving the energy efficiency of water supply systems. The proposed system is focused on increasing energy efficiency and optimizing hydraulic processes in water supply networks with variable flow rates. An automatic control algorithm has been developed that ensures pipeline pressure stabilization by continuous adjustment of the electric motor rotational speed in accordance with the current pressure value obtained from a pressure sensor.Special attention is paid to the cascade pump control principle, which enables effective coordination of pump operation with actual water consumption. Under low-load conditions, the required network pressure is provided by the operation of a single pump with adjustable speed, while the additional pump is automatically disconnected. This approach eliminates idle and low-efficiency operating modes, significantly reduces energy consumption, and decreases equipment wear by reducing the number of starts and prolonged operation at partial load.An experimental study of the energy and operating characteristics of a cascade pumping unit consisting of two induction motor drives with different rated parameters has been carried out. Control was implemented using variable-frequency regulation, which provides smooth adjustment of system flow rate and pressure depending on hydraulic load conditions. During the experiments, relationships between changes in consumed current, pressure, and rotational speed were obtained for various operating modes involving one or two pumps within the cascade system.Based on simulation modeling and experimental verification, quantitative relationships describing the influence of variable-frequency control on flow formation and pressure stability in the network were established. It is shown that the use of a frequency converter ensures system adaptability to dynamic load variations, reduces electrical energy losses, decreases starting stresses on electric drives, and generally enhances the reliability of pumping infrastructure operation.The obtained results have practical significance for the design of new and the modernization of existing water supply and irrigation systems, enabling improved energy performance, extended equipment service life, and higher quality of technological parameter control.Recieved: 29.12.2025.  Recieved: 01.03.2026. Accepted: 17.04.2026.
Keywords: pumping unit; frequency converter; automated electric drive; control program; PID controller